A high-performance tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material and preparation method thereof

The tin selenide/tin telluride/porous carbon nanofiber composite material prepared by electrospinning and high-temperature calcining process solves the problems of large volume changes and low conductivity during the cycle process of sodium ion battery electrode materials, achieving high performance and excellent electrochemical performance of the material.

CN114899379BActive Publication Date: 2025-03-25ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210527946.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-16
Publication Date
2025-03-25
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

The electrode material of sodium ion batteries changes greatly during the cycle, resulting in capacity attenuation and low conductivity, which hinders the application of SnSe and SnTe electrode materials.

Method used

Electrospinning and high-temperature calcining process are used to prepare tin selenide/tin telluride/porous carbon nanofiber composite materials to form a tightly woven three-dimensional network structure and uniformly embedded in the porous carbon nanofibers.

Benefits of technology

It effectively enhances the conductivity of SnSe/SnTe, suppresses volume expansion during charge and discharge, improves the diffusion rate of sodium ions, and significantly improves the cyclic stability and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114899379B_ABST
    Figure CN114899379B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-performance tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material and a preparation method thereof, which is prepared by electrospinning and high-temperature calcination process, and the material has a tightly woven three-dimensional mesh structure, and the porous carbon nanofiber is modified with SnSe / SnTe nanoparticles. The preparation method of the present invention is convenient and novel in conception, and the obtained composite material exhibits excellent sodium ion storage capacity, rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a high-performance tin selenide / tin telluride / porous carbon nanofiber composite material and application of the composite material as a negative electrode material for a sodium ion battery, and belongs to the field of carbon-based nanomaterials. Background Art

[0002] The increasing demand for lithium-ion batteries (LIBs) and the consumption of lithium resources make it impossible to meet the needs of future environmental sustainability and energy storage. In contrast, sodium-ion batteries (SIBs) are considered to be a promising alternative due to their abundant resource reserves and low cost. However, the large ionic radius leads to the cycle stability and rate performance of electrode materials that cannot meet the current commercialization needs. Therefore, the development of suitable electrode materials is very necessary and is also a current research hotspot. Among them, chalcogenides SnSe and SnTe have high specific capacity as alloy-type electrode materials and are considered to be very promising negative electrode materials. However, the severe volume change of alloy-type electrode materials during the cycle will cause inevitable capacity decay. In addition, the low conductivity also hinders the application of SnSe and SnTe electrode materials. Therefore, it is of far-reaching significance to improve the stability and kinetic properties of SnSe and SnTe negative electrode materials by optimizing the material composition and structure, and to construct SIBs negative electrodes with excellent electrochemical performance. Summary of the invention

[0003] The present invention aims to provide a tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material and a preparation method thereof which has convenient preparation method, low cost, novel concept, unique morphology and high performance, so as to improve the cycle stability and rate performance of the sodium ion battery.

[0004] In order to solve the technical problem, the present invention adopts the following technical solution:

[0005] The invention discloses a high-performance tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material, which has a tightly woven three-dimensional network structure, and tin selenide and tin telluride (SnSe / SnTe) nanoparticles are uniformly embedded in the porous carbon nanofibers.

[0006] The method for preparing the high-performance tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material of the present invention comprises the following steps:

[0007] Step 1, dispersing the PEO-PPO-PEO triblock copolymer in N-N-dimethylformamide, heating and stirring until uniform dispersion, then adding polyacrylonitrile and SnCl2·2H2O and continuing to heat and stir until dissolved, to obtain an electrospinning precursor solution;

[0008] Step 2, electrospinning the precursor solution obtained in step 1 to obtain a precursor film;

[0009] Step 3: Load the precursor film obtained in step 2, selenium and tellurium into a porcelain boat, and then pyrolyze them in a tubular furnace filled with N2 to obtain tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material.

[0010] Preferably, in step 1, the usage ratio of PEO-PPO-PEO triblock copolymer, NN dimethylformamide, polyacrylonitrile and SnCl2·2H2O is 0.3-0.5 g: 8-12 mL: 0.6-0.9 g: 1.3-1.7 g.

[0011] Preferably, in step 1, the temperature of the heating and stirring is 70-85°C.

[0012] Preferably, in step 2, the electrospinning method is: inject the precursor solution obtained in step 1 into a 10 mL syringe equipped with a 6-8# needle, at a rate of 0.5-0.7 mL / h –1 The flow rate was used to advance, aluminum foil was used as the collector, the distance between the needle and the collector was 15 cm, the applied voltage was 18 kV, and the obtained electrospun membrane was vacuum dried at 50-70°C for 12-24 h to obtain a precursor membrane.

[0013] Preferably, in step 3, the mass ratio of the precursor film, selenium and tellurium is 5.5-6.5:0.5-1.5:0.5-1.5.

[0014] Preferably, in step 3, the pyrolysis method is: firstly heating to 245-260°C and keeping warm for 4-6 hours, then heating to 650-750°C and keeping warm for 1-2 hours.

[0015] The beneficial effects of the present invention are embodied in:

[0016] The sodium ion battery negative electrode material of the present invention is obtained by electrostatic spinning and high temperature calcination process, the method is convenient and novel, the obtained material has a three-dimensional porous carbon fiber network structure woven tightly, and tin selenide / tin telluride (SnSe / SnTe) nanoparticles are uniformly embedded in the porous carbon nanofibers. The tin selenide / tin telluride / porous carbon nanofiber composite material can effectively enhance the electrical conductivity of SnSe / SnTe and inhibit its volume expansion during charging and discharging. At the same time, the porous carbon fiber network can enhance the diffusion rate of ions, so that the SnSe / SnTe / porous carbon nanofiber material has excellent sodium ion storage capacity, cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1This is a SEM photo of the SnSe / SnTe / porous carbon nanofiber composite material obtained in Example 1 of the present invention;

[0018] Figure 2 TEM photo of the SnSe / SnTe / porous carbon nanofiber composite material obtained in Example 1 of the present invention ( Figure 2 (a)) and HRTEM images ( Figure 2 (b));

[0019] Figure 3 The SEM photos of the PAN-P123-SnCl2·2H2O precursor spinning membrane material used as a comparison in Example 1 of the present invention, wherein (a) and (b) correspond to different magnifications;

[0020] Figure 4 This is the X-ray diffraction spectrum of the SnSe / SnTe / porous carbon nanofiber composite material obtained in Example 1 of the present invention;

[0021] Figure 5 is the N2 adsorption / desorption isotherm of the SnSe / SnTe / porous carbon nanofiber composite material obtained in Example 1 of the present invention;

[0022] Figure 6 This is the thermogravimetric curve of the SnSe / SnTe / porous carbon nanofiber composite material obtained in Example 1 of the present invention;

[0023] Figure 7 The figure is a comparison of the battery rate performance of the SnSe / SnTe / porous carbon nanofiber composite material (SnSe / SnTe@N-CNFs) obtained in Example 1 of the present invention, the SnSe / porous carbon nanofiber (SnSe@N-CNFs) and the SnTe / porous carbon nanofiber material (SnTe@N-CNFs);

[0024] Figure 8 This is a comparison chart of battery cycle performance of the SnSe / SnTe / porous carbon nanofiber composite material (SnSe / SnTe@N-CNFs) obtained in Example 1 of the present invention, SnSe / porous carbon nanofiber (SnSe@N-CNFs), and SnTe / porous carbon nanofiber material (SnTe@N-CNFs);

[0025] Fig. 9 The SnSe / SnTe / porous carbon nanofiber composite material (SnSe / SnTe@N-CNFs) and SnSe / porous carbon nanofiber (SnSe@N-CNFs) obtained in Example 1 of the present invention and the SnTe / porous carbon nanofiber material (SnTe@N-CNFs) were prepared at 1Ag. –1 Comparison of cycling performance under high current density. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned purposes, features and advantages of the present invention more understandable, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field can make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0027] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0028] Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources.

[0029] The electrochemical performance tests of the sodium ion batteries in the following examples were all completed by the NEWARE battery testing system (test voltage 0.01V-3.0Vvs.Na + / Na).

[0030] Example 1

[0031] In this embodiment, a tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material with a high performance structure is prepared according to the following steps:

[0032] Step 1, weigh 0.4g PEO-PPO-PEO triblock copolymer (P123, MW = 5800, Aladdin) and disperse it in 12mL NN dimethylformamide (DMF, >99.9%, McLean), heat and stir at 80°C until dissolved; then, add 0.6g polyacrylonitrile (PAN, MW = 150,000, McLean) and 1.57g SnCl2·2H2O (7mmol) (McLean) and continue heating and stirring until dissolved to obtain an electrospinning precursor solution.

[0033] Step 2: Inject the precursor solution obtained in step 1 into a 10 mL syringe equipped with a 8# needle at a rate of 0.6 mL h –1 The flow rate was set at 150 ℃, aluminum foil was used as the collector, the distance between the needle and the collector was 15 cm, the applied voltage was 18 kV, and the obtained electrospun membrane was vacuum dried at 60°C for 12 hours to obtain a precursor membrane.

[0034] Step 3, the precursor film obtained in step 2 is loaded into a porcelain boat with selenium and tellurium in a mass ratio of 6:1:1, and then pyrolyzed in a tubular furnace filled with N2 (first heated to 250°C and kept warm for 5 hours, then heated to 700°C and kept warm for 1 hour), thereby obtaining a SnSe / SnTe / porous carbon fiber composite material as a negative electrode material for a sodium ion battery.

[0035] For comparison, SnTe / porous carbon nanofiber and SnSe / porous carbon nanofiber materials are also prepared in this embodiment. The method is the same as the preparation method of the above-mentioned SnSe / SnTe / porous carbon nanofiber composite material, with the only difference being that the weight ratio of the precursor film loaded into the porcelain boat to selenium or tellurium is 3:1.

[0036] Figure 1 is a SEM photo of the SnSe / SnTe / porous carbon fiber composite material obtained in this example, Figure 2 TEM image of the SnSe / SnTe / porous carbon fiber composite material obtained in this example ( Figure 2 (a)) and HRTEM images ( Figure 2 (b)), it can be seen that the SnSe / SnTe / porous carbon fiber composite material presents an obvious fiber morphology as a whole, with a diameter of about 200nm, and is tightly woven into a three-dimensional network configuration. At the same time, SnSe / SnTe nanoparticles are uniformly embedded in the porous carbon fibers.

[0037] Figure 3 This is the SEM photo of the PAN-P123-SnCl2·2H2O precursor spinning membrane material used as a comparison in this embodiment. It can be seen that the precursor membrane has a fiber cross-linked structure.

[0038] Figure 4 The X-ray diffraction spectrum of the SnSe / SnTe / porous carbon fiber composite material obtained in this embodiment shows that the diffraction peaks of the composite material correspond to the characteristic peaks of the SnSe (JCPDS no.89-0233) and SnTe (JCPDS no.46-1210) standard cards. Figure 1 and Figure 2 The electron microscope picture shows that the SnSe / SnTe / porous carbon fiber composite material was successfully prepared in this example.

[0039] Figure 5 The N2 adsorption / desorption isotherm curve of the SnSe / SnTe / porous carbon fiber composite material obtained in this example shows that the obtained composite material has porous characteristics and a specific surface area of ​​177.39 m 2 g -1 , with an average pore size of about 0.989 nm. This porous property not only provides additional active sites for the storage of sodium ions, but also shortens the diffusion path of sodium ions, thereby improving the discharge capacity and kinetic performance of SIBs.

[0040] Figure 6This is the thermogravimetric curve of the SnSe / SnTe / porous carbon fiber composite material obtained in this example. As can be seen from the figure, the SnSe / SnTe / porous carbon fiber composite material will react chemically with the air under high temperature air atmosphere conditions. From this, the carbon content in the SnSe / SnTe / porous carbon fiber composite material can be calculated, and the specific mass percentage can be quantitatively determined to be about 44wt.%.

[0041] The SnSe / SnTe / porous carbon fiber composite material of this embodiment and the comparative SnSe / porous carbon fiber and SnTe / porous carbon fiber materials were mixed and ground with Ketjen black and binder (PVDF) in a weight ratio of 8:1:1, and evenly applied on the surface of copper foil. After vacuum drying at 90°C, they were sliced ​​and used as working electrodes for sodium ion batteries. Glass fiber GF / D is the diaphragm, the metal sodium sheet is the counter electrode, and the electrolyte is 1M NaCF3SO3 solution. The button battery 2032 is assembled in the order of negative electrode shell, counter electrode, diaphragm, electrolyte, working electrode, gasket, spring sheet, and positive electrode shell. Subsequently, the battery was tested after standing for several hours at room temperature. The tests of relevant electrochemical properties were all carried out in the NEWARE battery test system.

[0042] Figure 7 The battery rate performance of the SnSe / SnTe / porous carbon fiber composite material obtained in this example is compared with that of the SnSe / porous carbon fiber and SnTe / porous carbon fiber materials. The test rates are 0.1, 0.2, 0.5, 1, 1.5, 2, and 0.1Ag, respectively. –1 As shown in the figure, SnSe / SnTe / porous carbon fiber composite material has better rate performance than the other two groups, even at 2Ag –1 The high reversible capacity of sodium storage (250 mAh g –1 ).

[0043] Figure 8 The SnSe / SnTe / porous carbon fiber composite material obtained in this embodiment and the SnSe / porous carbon fiber and SnTe / porous carbon fiber materials are obtained in 0.1Ag –1 Comparison of cycling performance under current density. As shown in the figure, after 100 cycles of charge and discharge, the reversible specific capacity of SnSe / SnTe / porous carbon fiber composite material can still be maintained at 480 mAh g –1 , much higher than the comparison materials, showing better cycle performance.

[0044] Fig. 9 The SnSe / SnTe / porous carbon fiber composite material obtained in this embodiment and the SnSe / porous carbon fiber and SnTe / porous carbon fiber materials are obtained at 1Ag. –1Comparison of cycling performance under high current density. As shown in the figure, after 200 cycles of charge and discharge, the cyclic reversible specific capacity of SnSe / SnTe / porous carbon fiber composite material is still maintained at 250mAh g –1 , showing better cycle stability performance.

[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material, characterized in that: The steps include: Step 1, dispersing the PEO-PPO-PEO triblock copolymer in N-N-dimethylformamide, heating and stirring until uniform dispersion, then adding polyacrylonitrile and SnCl2·2H2O and continuing to heat and stir until dissolved, to obtain an electrospinning precursor solution; Step 2, electrospinning the precursor solution obtained in step 1 to obtain a precursor film; Step 3: Load the precursor film obtained in step 2 with selenium and tellurium into a porcelain boat, and then perform pyrolysis in a tubular furnace filled with N2 to obtain a tin selenide / tin telluride / porous carbon nanofiber sodium ion battery negative electrode material, wherein the sodium ion battery negative electrode material has a tightly woven three-dimensional network structure, and tin selenide nanoparticles and tin telluride nanoparticles are uniformly embedded in the porous carbon nanofibers.

2. The preparation method according to claim 1, characterized in that: In step 1, the usage ratio of PEO-PPO-PEO triblock copolymer, NN dimethylformamide, polyacrylonitrile and SnCl2·2H2O is 0.3~0.5g:8~12mL:0.6~0.9g:1.3~1.7g.

3. The preparation method according to claim 1, characterized in that: In step 1, the temperature of the heating and stirring is 70-85°C.

4. The preparation method according to claim 1, characterized in that: In step 2, the electrospinning method is: Inject the precursor solution obtained in step 1 into a 10 mL syringe equipped with a 6~8# needle at a rate of 0.5~0.7 mL / h. –1 The flow rate was used to advance, aluminum foil was used as the collector, the distance between the needle and the collector was 15 cm, the applied voltage was 18 kV, and the obtained electrospun membrane was vacuum dried at 50-70°C for 12-24 hours to obtain a precursor membrane.

5. The preparation method according to claim 1, characterized in that: In step 3, the mass ratio of the precursor film, selenium and tellurium is 5.5~6.5:0.5~1.5:0.5~1.

5.

6. The preparation method according to claim 1, characterized in that: In step 3, the pyrolysis method is: firstly heating to 245-260°C and keeping the temperature for 4-6 hours, then heating to 650-750°C and keeping the temperature for 1-2 hours.

Citation Information

Patent Citations

  • Electrostatic spinning preparation method of self-supporting SnTe / C nanofiber

    CN110061219A

  • Sodium secondary battery, method for manufacturing negative electrode for sodium secondary battery, and electric equipment

    JP2013054987A